Interleukin-1β suppression dampens inflammatory leucocyte production and uptake in atherosclerosis . Issue 13 (28th October 2021) - Hettwer, Jan; Hinterdobler, Julia; Miritsch, Benedikt; Deutsch, Marcus-André; Li, Xinghai; Mauersberger, Carina; Moggio, Aldo; Braster, Quinte; Gram, Hermann; Robertson, Avril A B; Cooper, Matthew A; Groß, Olaf; et al.
Abstract: Aims: Targeting vascular inflammation represents a novel therapeutic approach to reduce complications of atherosclerosis. Neutralizing the pro-inflammatory cytokine interleukin-1β (IL-1β) using canakinumab, a monoclonal antibody, reduces the incidence of cardiovascular events in patients after myocardial infarction (MI). The biological basis for these beneficial effects remains incompletely understood. We sought to explore the mechanisms of IL-1β-targeted therapies. Methods and results: In mice with early atherosclerosis ( ApoE –/– mice on a high-cholesterol diet for 6 weeks), we found that 3 weeks of NACHT, LRR, and PYD domains-containing protein 3 (NLRP3)-inflammasome inhibition or anti-IL-1β treatment (using either MCC950, an NLRP3-inflammasome inhibitor which blocks production and release of active IL-1β, or a murine analogue of canakinumab) dampened accumulation of leucocytes in atherosclerotic aortas, which consequently resulted in slower progression of atherosclerosis. Causally, we found that endothelial cells from atherosclerotic aortas lowered expression of leucocyte chemoattractants and adhesion molecules upon NLRP3-inflammasome inhibition, indicating that NLRP3-inflammasome- and IL-1β-targeted therapies reduced blood leucocyte recruitment to atherosclerotic aortas. In accord, adoptive transfer experiments revealed that anti-IL-1β treatment mitigated blood myeloid cell uptake to atherosclerotic aortas. We further report that anti-IL-1β treatment and NLRP3-inflammasome inhibition reduced inflammatory leucocyte supply by decreasing proliferation of bone marrow haematopoietic stem and progenitor cells, demonstrating that suppression of IL-1β and the NLRP3-inflammasome lowered production of disease-propagating leucocytes. Using bone marrow reconstitution experiments, we observed that haematopoietic cell-specific NLRP3-inflammasome activity contributed to both enhanced recruitment and increased supply of blood inflammatory leucocytes. Further experiments that queried whether anti-IL-1β treatment reduced vascular inflammation also in post-MI accelerated atherosclerosis documented the operation of convergent mechanisms (reduced supply and uptake of inflammatory leucocytes). In line with our pre-clinical findings, post-MI patients on canakinumab treatment showed reduced blood monocyte numbers. Conclusions: Our murine and human data reveal that anti-IL-1β treatment and NLRP3-inflammasome inhibition dampened vascular inflammation and progression of atherosclerosis through reduced blood inflammatory leucocyte (i) supply and (ii) uptake into atherosclerotic aortas providing additional mechanistic insights into links between haematopoiesis and atherogenesis, and into the beneficial effects of NLRP3-inflammasome- and IL-1β-targeted therapies. Graphical Abstract: